Migrants in modern France : population mobility in the later nineteenth and twentieth centuries - Ogden, Philip E. (Philip Ernest), 1949-; White, Paul E., 1950- (Unwin Hyman, 1989)
A discussion of the structure and role of migration flows affecting France from 1850 to the present day. It covers both internal and international movements and consideration is given both to broad macro-scale analysis and more detailed micro-scale investigations.